A Bio-inspired Grasp Stiffness Control for Robotic Hands - Ruiz Garate, Virginia; Pozzi, Maria; Prattichizzo, Domenico; Ajoudani, Arash (Frontiers in Robotics and AI, 2018)
This work presents a bio-inspired grasp stiffness control for robotic hands based on the concepts of Common Mode Stiffness and Configuration Dependent Stiffness. Using an ellipsoid representation of the desired grasp stiffness, the algorithm focuses on achieving its geometrical features. Based on preliminary knowledge of the fingers workspace, the method starts by exploring the possible hand poses that maintain the grasp contacts on the object. This outputs a first selection of feasible grasp configurations providing the base for the Configuration Dependent Stiffness control. Then, an optimization is performed to find the minimum joint stiffness (Common Mode Stiffness control) that would stabilize these grasps. This joint stiffness can be increased afterwards depending on the task requirements. The algorithm finally chooses among all the found stable configurations the one that results in a better approximation of the desired grasp stiffness geometry (Configuration Dependent Stiffness). The proposed method results in a reduction of the control complexity, needing to independently regulate the joint positions, but requiring only one input to produce the desired joint stiffness. Moreover, the usage of the fingers pose to attain the desired grasp stiffness results in a more energy-efficient configuration than only relying on the joint stiffness (i.e. joint torques) modifications. The control strategy is evaluated using the fully actuated Allegro Hand while grasping a wide variety of objects. Different desired grasp stiffness profiles are selected to exemplify several stiffness geometries.